Effect of different storage conditions in recalcitrant seeds of holm oak (Quercus ilex L.) during germination - Pasquini, S; Braidot, E; Petrussa, E; Vianello, A (Seed Science and Technology, 2011)
The effect of three different storage treatments on holm oak (Quercus ilex L.) acorns was examined over a period of twelve months. Acorns from two seed lots were stored at 3°C with three different treatments: acorns mixed with peat inside a can with a pierced pipe through the middle, acorns mixed in moistened sand, or acorns inside polyethylene bags without medium. Samples were collected every two months and were analyzed for moisture content, germination and electrolyte leakage. Storage of acorns in polyethylene bags maintained the high seedling percentage usually observed after harvest in germination tests. The acorns stored mixed with peat or sand failed to maintain the germination vigour observed at harvest. Electrolyte leakage was significantly higher for acorns stored in peat rather than for the other two treatments. However, acorns stored in sand and in peat had a higher level of moisture content than those kept in polyethylene bags. These results suggest that storage of acorns from the recalcitrant holm oak in polyethylene bags could preserve the acorn germination over a longer period of time with respect to the usual methods.
Keywords: acorn storage conditions; electrolyte leakage; germination; Holm oak; Moisture content; recalcitrant seed (voyant)

Comportement physiologique des glands de chêne liège (Quercus suber L.) durant leur conservation et variabilité inter-individus producteurs - Merouani, Hachemi; Branco, Carmen; Almeida, Maria Helena; Pereira, João S. (Ann. For. Sci., 2001)
The mature acorns were harvested on twelve selected trees from a cork oak population in Southern Portugal (Herdade da Palma). After drying, the seed lots were stored on three types bags (polyethylene with 30 mm and 50 mm thick and plastic mesh), for six months at 0 oC. At the time of natural dissemination, the acorns from the majority of the trees from the same population were under the same state of morphological and physiological maturity. The moisture content was about 44-47% and a germination rate above 92% . At this time, the germination was very slow because of the existent embryonic dormancy that seems to be dependent on the individual trees. During the storage, germination rate is improved. This might be explained by the breaking dormancy during storage. The mean germination time was on an average 10 days for fresh seeds and decreased to about 4 days after 6 months storage. A relationship between viability and seed moisture content was observed. The Mean Germination Time of dried seed and stored seed for 4 months in plastic mesh bag increased to about 13 days. The germination capacity was strongly decreased when the seed moisture content was below 30%
Keywords: electrolyte leakage; germination; Moisture content; Quercus suber; seed; storage

Comportement physiologique des glands de chêne liège (Quercus suber L.) durant leur conservation et variabilité inter-individus producteurs - Merouani, Hachemi; Branco, Carmen; Almeida, Maria Helena; Pereira, João S (Ann. For. Sci., 2001)
The mature acorns were harvested on twelve selected trees from a cork oak population in Southern Portugal (Herdade da Palma). After drying, the seed lots were stored on three types bags (polyethylene with 30 mm and 50 mm thick and plastic mesh), for six months at 0 oC. At the time of natural dissemination, the acorns from the majority of the trees from the same population were under the same state of morphological and physiological maturity. The moisture content was about 44-47% and a germination rate above 92% . At this time, the germination was very slow because of the existent embryonic dormancy that seems to be dependent on the individual trees. During the storage, germination rate is improved. This might be explained by the breaking dormancy during storage. The mean germination time was on an average 10 days for fresh seeds and decreased to about 4 days after 6 months storage. A relationship between viability and seed moisture content was observed. The Mean Germination Time of dried seed and stored seed for 4 months in plastic mesh bag increased to about 13 days. The germination capacity was strongly decreased when the seed moisture content was below 30%
Keywords: electrolyte leakage; germination; Moisture content; Quercus suber; seed; storage